THE INFLUENCE OF WORK CLIMATE ON JOB SATISFACTION IN FOREIGN CAPITAL COMPANIES IN THE MANUFACTURING SECTOR - Diar Fachmi Rachmat Chaidar (Jurnal Ekonomi Bisnis Manajemen dan Akuntansi (JEBISMA), 2023)
Abstract The work environment is important in encouraging employees to be enthusiastic about working. Creating a good work environment is one of the many systems a company must use to run a large business. Therefore, this research aims to find out how the work environment influences job satisfaction in foreign companies working in the manufacturing industry. Data collection was carried out through descriptive and verification research. The results showed that most respondents felt and accepted the organization's policies, practices, and procedures. Therefore, the conclusion shows that the work environment only influences job satisfaction marginally. Keyword : Job Climate, Job Satisfaction, Manufacturing Sector Foreign Capital Companies